On-farm corn stover and cover crop residue recycling with biostimulant Re-Gen increases corn yields and resultant milk yields in multi-year dairy cattle farm trials - Gibson, William S.; Ziobron, Amy S.; Olson, Noah E.; Neher, Deborah A.; Smith, Charles F.; Holden, Victoria I. (Frontiers in Agronomy, 2024)
IntroductionThere is a need to rebuild soil health by implementing regenerative agricultural practices across cropping systems dependent on agrochemicals, such as in United States corn production. One increasingly utilized regenerative practice is the application of biostimulants, or microbial inoculants that can rebuild soil health and productivity. In this study, we describe results from a multi-year corn trial conducted to quantify the impact of Re-Gen, a biostimulant invented to recycle plant biomass and increase nutrient bioavailability in the soil.MethodsRe-Gen was applied across four fields (VA01, BH01, VA04, and LA05) at a dairy cattle farm in Ferrisburgh, VT.ResultsOver the two consecutive years (2022-2023) of the trial, Re-Gen application on corn stover and cover crop residues increased ear corn yield by 24% and corn silage yield by 12.5-30%, depending on the field. Analysis of soil nutrients and plant tissues showed increased nutrients, particularly in field LA-05. Multi-year Re-Gen application increased yield and generated additional economic value, indicating that the effects of Re-Gen do not diminish with multiple applications. The increased corn silage yield correlated to increased potential milk yield from cows fed silage grown in Re-Gen-treated fields. Further investigation into the mechanism suggests that increased phosphatase production Re-Gen could contribute to increased phosphorus bioavailability in the soil and uptake in the tissue, potentially increasing yields.DiscussionThese results highlight the potential for Re-Gen to foster regenerative agriculture processes on cropland and livestock farms while also increasing corn and milk yield and, therefore, revenue for corn farmers in the United States and for similar cropping systems worldwide.